2014
DOI: 10.1007/s00167-014-3112-4
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the axillary nerve to the subacromial bursa and the area around the long head of the biceps tendon

Abstract: These results would be useful to consider the cause of the shoulder pain or to prevent the residual pain after the biceps tenodesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…The estimated contribution of the AN to the totality of the shoulder joint innervation is variable. Near the quadrangular space, the main trunk gives direct articular branches to the inferior area (see also Tran et al, ) of the shoulder joint capsule, with other articular branches arising from the branch to the teres minor or appearing in the posterolateral aspect of the capsule after piercing the connective tissue of the tendon of the BB (Nasu et al, ; Eckmann et al, ). Some authors mention a single articular branch (Duparc et al, ), which they call the joint nerve (JN), while others use more general terms such as articular branch or capsular branch.…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…The estimated contribution of the AN to the totality of the shoulder joint innervation is variable. Near the quadrangular space, the main trunk gives direct articular branches to the inferior area (see also Tran et al, ) of the shoulder joint capsule, with other articular branches arising from the branch to the teres minor or appearing in the posterolateral aspect of the capsule after piercing the connective tissue of the tendon of the BB (Nasu et al, ; Eckmann et al, ). Some authors mention a single articular branch (Duparc et al, ), which they call the joint nerve (JN), while others use more general terms such as articular branch or capsular branch.…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…Shoulder pain is usually caused by the anterior, lateral, and posterior of the shoulder region as well as muscle, ligament, bursa, and capsule which constitute the shoulder joint [ 3 , 4 ]. Patients with a shoulder disorder usually complain of pain on the lateral region of the shoulder that is often caused by a bursa [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gardner7 was the first to report the innervation of GHJ from all four articular branches (SSN, AN, LPN and NS) 7. More recently, Nasu et al 14 found an articular branch terminating in the transverse humeral ligament that originated from the anterior division of AN,14 and Eckmann et al 16 found additional articular branches from SSN that coursed along the superior border of the spine of scapula to supply the posterosuperior GHJ capsule 16. However, in the current study, branches of the musculocutaeneous nerve reported by Wrete (1948) were not found 8…”
Section: Discussionmentioning
confidence: 99%